Hubungan Antara Kualitas Pelayanan dengan Kepuasan Pasien Poli Gigi dan Mulut di Rumah Sakit (Studi Literasi) - Nuryanti Nuryanti; Selvia Magdalena; Gregorius Yoga Panji Asmara; Vip Paramarta (Jurnal Rumpun Ilmu Kesehatan, 2024)
Improving the quality of service in hospitals is an important factor to support patient satisfaction. Patient loyalty is determined by the quality of service, so the quality of service must be improved. The purpose of this article is to find out what factors can influence the quality of service in a hospital. The influencing factors are tangible, realistic, responsive, assurance, and empathy. Patient satisfaction is an important component of various health service parameters because patient assessment can be a measure of the quality of health services. Cases of dental and oral disease are high throughout the world, accompanied by an increase in prevalence in Indonesia based on Riskesdas results from 2007 to 2018 and high rates of self-treatment of dental and oral diseases.